2020 Transnational Engineering Education Using Technology (TREET) 2020
DOI: 10.1109/treet50959.2020.9189749
|View full text |Cite
|
Sign up to set email alerts
|

Solar Thermal Collector Education using Polysun Simulations Software

Abstract: There are a variety of solar thermal collectors available in the market today. These collectors are typically manufactured in diverse countries and have different performance characteristics. For homeowners and commercial solar solution providers, it is important to know how these collectors will perform to ensure maximum return on investment. Therefore, engineers and technicians need to be trained into how different collectors will perform in different locations. In this article, we demonstrate how a Swiss si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…According to Witzig and Kunath [65], this Switzerland-origin simulations software package is comparatively user-friendly, with a vast database of system components. Abdel-Aty et al [66] investigated the usability and accuracy of Polysun and reported that it can be used as an effective tool in educational courses on solar thermal energy systems using diverse simulation scenarios and results visualization. Azhar-Kareem et al [67] investigated the variation of tilt angle (0 • to 90 • ) on the performance of a solar collector using Polysun and reported that the optimum value is around 40 • for the selected location.…”
mentioning
confidence: 99%
“…According to Witzig and Kunath [65], this Switzerland-origin simulations software package is comparatively user-friendly, with a vast database of system components. Abdel-Aty et al [66] investigated the usability and accuracy of Polysun and reported that it can be used as an effective tool in educational courses on solar thermal energy systems using diverse simulation scenarios and results visualization. Azhar-Kareem et al [67] investigated the variation of tilt angle (0 • to 90 • ) on the performance of a solar collector using Polysun and reported that the optimum value is around 40 • for the selected location.…”
mentioning
confidence: 99%